Neutral, heteroleptic copper(i)-4H-imidazolate complexes: synthesis and characterization of their structural, spectral and redox properties. Issue 11 (12th February 2016) - Schulz, M.; Dröge, F.; Herrmann-Westendorf, F.; Schindler, J.; Görls, H.; Presselt, M.
Abstract : Facile synthetic access to four novel, neutral, heteroleptic copper(i )-complexes, incorporating 4 H -imidazolates as well as the phosphane ligands XantPhos and DPEPhos is reported. Abstract : Facile synthetic access to four novel, neutral, heteroleptic copper(i )-complexes, incorporating 4 H -imidazolates as well as the phosphane ligands XantPhos and DPEPhos is reported. The complexes were characterized in the solid state as well as in solution by means of single crystal X-ray diffraction as well as NMR spectroscopy, mass spectrometry and elemental analysis. The copper(i )-4 H -imidazolate complexes show a broad intense absorption that spans almost the entire visible range. TD-DFT calculations revealed the charge transfer character of the underlying transitions. NMR as well as electrochemical investigations and UV-Vis absorption suggest a polarization of the complexes with the negative charge pushed towards the 4 H -imidazolate moiety.